Productivity of soya crops under application of different types of fungicides and inoculant - Mostoviak, I.; Kravchenko, O. (Quarantine and plant protection, 2019)
Goal. Fungicide application fungicides, applied separately and at the background of using inoculum Rhizoactive, on the formation of yielding capacity and some structural parameters of soy crops. According to the set goal, the task was to select the most effective fungicides to fight diseases in the crops, when they are applied separately and at the background of seed inoculation with Rhizoactive. Methods. Field and laboratory. Results. It has been established that the formation of the yielding capacity of soya and indexes of crops structure depends on the fungicides type and their application against the background of using inoculant and without it. It has been proved that the highest productivity of soya crops formed in the variants of the experiment with the application of Impact K, 0.8 l/ ha and Coronet 300 SC КС, 0.8 l/ha against the background of treatment of soya seeds with Rhizoactive. Conclusions. Application of fungicides Akanto Plus 28 KC, 1.0 l/ha, Amistar Extra 280 SC, KC, 0.75 l/ha, Bamper Super 490, KE, 1.5 l/ ha, Impact K, 0.8 l/ha, Koronet 300 SC, KC, 0.5 l/ha in the crops of soy at the background of pre-sowing seed treatment with inoculum leads to the increase of yielding capacity of crops by 11—15% and improved structure of crops, which is, on the one hand, provided by the improving phytosanitary state of soy crops under the action of fungicides, and on the other hand, by the nutrition of plants at the background of activation of legume inoculum.